Predictors of outcomes following liver transplant in hepatopulmonary syndrome: An OPTN database analysis. (December 2021) - Jose, Arun; Shah, Shimul A.; Anwar, Nadeem; Jones, Courtney R.; McCormack, Francis X.; Sherman, Kenneth E.; Elwing, Jean M.
Abstract: Hepatopulmonary syndrome (HPS) is a type of pulmonary vascular disease occurring exclusively in those with underlying liver disease, associated with significant mortality in patients awaiting liver transplantation (LT). LT is curative in HPS, and these patients are granted Model for End Stage Liver Disease (MELD) exception points to expedite LT. The purpose of this study is to use multivariable competing risk Accelerated Failure Time models and propensity matching to examine the relationship between pre-LT hypoxemia and post-LT outcomes in HPS. We performed a retrospective cohort study of UNOS/OPTN database of all adult patients undergoing LT between January 1, 2006 and January 12, 2020. Pre-LT PaO2 was significantly associated with post-LT mortality in HPS, with each 1 mmHg increase in PaO2 significantly decreasing the risk of post-LT mortality (coefficient 0.039, HR = 0.95, p = 0.001). HPS patients with a pre-LT PaO2 < 54 mmHg demonstrated increased mortality following LT as compared to matched non-HPS cirrhotic patients. We conclude that HPS patients with a PaO2, 54 mmHg are at increased risk of post-LT mortality and may identify high-risk patients who would benefit from additional resources during LT, and that the effects of HPS MELD exception points to optimize post-LT outcomes should be continuously re-evaluated. Highlights: Mortality after transplant in HPS is associated with severity of hypoxemia. The threshold at which post-transplant mortality increases is unclear. Propensity matching analysis identified PaO2<54 mmHg as high risk in HPS. HPS had lower graft failure after transplant than non-HPS cirrhosis. High-risk HPS may benefit from transplant at experienced high-volume centers.